ʼA rhaṅʻ Janakābhivaṃsa e* ta bhava sāsanā - Janakābhivaṃsa, Ashin, 1899-1977 (Praññʻ thoṅʻ cu Chuirhayʻlacʻ Sammata Mranʻ mā Nuiṅʻ ṅaṃ toʻ, Sāsanā reʺ Ūʺ cīʺ Ṭhāna, 1984)
Festschrift honoring a Burmese Buddhist monk; comprises his works, with an introductory on his life and teachings.